Sodium flow measurement in large pipelines of sodium cooled fast breeder reactors with bypass type flow meters. (January 2016) - Rajan, K.K.; Jayakumar, T.; Aggarwal, P.K.; Vinod, V.
Highlights: Bypass type permanent magnet flow meters are more suitable for sodium flow measurement. A higher sodium velocity through the PMFM sensor will increase its sensitivity and resolution. By modifying the geometry of bypass line, higher sodium velocity through sensor is achieved. With optimized geometry the sensitivity of bypass flow meter system was increased by 70%. Abstract: Liquid sodium flow through the pipelines of sodium cooled fast breeder reactor circuits are measured using electromagnetic flow meters. Bypass type flow meter with a permanent magnet flow meter as sensor in the bypass line is selected for the flow measurement in the 800 NB main secondary pipe line of 500 MWe Prototype Fast Breeder Reactor (PFBR), which is at the advanced stage of construction at Kalpakkam. For increasing the sensitivity of bypass flow meters in future SFRs, alternative bypass geometry was considered. The performance enhancement of the proposed geometry was evaluated by experimental and numerical methods using scaled down models. From the studies it is observed that the new configuration increases the sensitivity of bypass flow meter system by around 70%. Using experimentally validated numerical tools the volumetric flow ratio for the bypass configurations is established for the operating range of Reynolds numbers.